Mechanisms and biological effects of Caffeine on substrate metabolism homeostasis: A systematic review - Luiz Augusto da Silva, Jéssica Wouk, Vinícius Müller Reis Weber, Camila da Luz Eltchechem, Pablo de Almeida, Julio Cesar Lacerda Martins, Carlos Ricardo Maneck Malfatti, Raul Osiecki (Journal of Applied Pharmaceutical Science, 2017)
Objective: This review aims to elucidate the possible effects of caffeine over homeostasis mechanism of energetic subtracts metabolism. Methods: The study was carried out in systematic review form and its sample comprised six scientific papers published in academic journals. Only the studies involving soccer players (professionals and amateurs, except goalkeepers) were included in this review.Results: Caffeine was able to increase insulin and serum glycemia levels, after oral glucose tolerance test (OGTT), demonstrating that caffeine alters blood glucose maintenance in diabetic men. A decrease of insulin sensibility evaluated by insulin sensibility index (ISI) rates was observed. Also showed that the administration of caffeine was able to control the catecholamine levels. Nevertheless, demonstrated that long-term consumption of caffeine may be efficient in controlling glucose and adiponectin levels, which would be good for the prevention as well as for the associated complication of diabetes mellitus.Conclusion: Caffeine is one of the active compounds of coffee and its consumption is being suggested as benefic over glucose tolerance. Albeit, acute and chronic studies are demonstrating controversial results, showing differences in blood glucose levels, such as enhancement, reduction and also, no changes, after the consumption of different doses of caffeine. The mechanism to explain this events is yet unknown, however it is suggested that caffeine may act over insulin clearance. Some studies are aiming to evaluate the action of caffeine over insulin sensibility. Caffeine may act reducing insulin sensibility over its receptors.
Keywords: Diabetes, Caffeine, Exercise, Glycemia.